Using d2d for Writing XML - Markus Lepper; Baltasar Trancón y Widemann (Journal of the Text Encoding Initiative)
The textual structures of notes and publications in music theory and musical analysis bring challenging requirements: how to include music notation excerpts, graphics, and even combinations thereof into the typeset flow of paragraphs and the workflow, and how to integrate navigable references to these and to single domain entities into running text. Furthermore, dynamic interactive documents can be useful for presenting complicated interdependencies to the reader more clearly, far beyond conventional paper publication. D2d is a text format definition and compiler-based implementation to allow domain experts and novelists to write texts in the flow of authoring, with minimal technical interference, that are nevertheless valid XML documents. The multiNotes text architecture and processing pipeline described here is based on d2d and standard technologies (XSLT, ECMAScript, lilyPond, PostScript, etc.) and addresses these issues. It can be reused as it is for further projects. Being standard XML, switching the backend to other formats (like TEI plus MEI) seems promising—not affecting the underlying design criteria. All source texts are in the public domain; a publication on an open-source code repository is in preparation.